Clumped Isotope Data of NE Greenland samples from Salomon et al., submitted to Solid Earth - Salomon, Eric (IEDA: EarthChem Library, 2020)
Abstract: This dataset contains D47, d18O, and d13C data from 18 samples of carbonate veins and cements from the Dombjerg Fault and hanging wall clastic Lindemans Bugt Formation in the Wollaston Forland, NE Greenland. The dataset has been used to assess along-fault fluid flow and diagenesis of fault-proximal sediments. In addition, replicate-level raw data is provided to allow for reprocessing of the data. Other Description: Salomon, E., Rotevatn, A., Kristensen, T. B., Grundvåg, S.-A., Henstra, G. A., Meckler, A. N., Albert, R., & Gerdes, A. (2020). Fault-controlled fluid circulation and diagenesis along basin-bounding fault systems in rifts – insights from the East Greenland rift system. Solid Earth, 11(6), 1987–2013.